Peran Gaya Kepemimpinan Pemilik UMKM terhadap Kinerja Ekonomi Usaha di Era Digital - Faizal, Ahmad; Mubarok, Achmad Hadi; Purnomo, Hari (CV. Lentera Literasi Indonesia, 2025)
This study aims to examine the role of leadership styles of MSME (Micro, Small, and Medium Enterprises) owners on business economic performance in the digital era, with a focus on MSME actors in Banyuwangi Regency. The background of this research is based on the importance of adaptive leadership in managing small and medium enterprises affected by technological changes and digital consumption patterns. This study employs a descriptive qualitative approach with data collection methods including literature review, direct observation, and in-depth interviews with ten MSME owners actively using digital platforms. The findings reveal that transformational leadership style significantly contributes to business economic growth through motivation, innovation, and technology adoption. Meanwhile, democratic leadership style encourages employee involvement and operational efficiency through participative decision-making and a collaborative work culture. In contrast, authoritarian leadership style hinders the digital adaptation process and negatively impacts business performance. In conclusion, open, participative, and transformative leadership styles are key to the success of MSMEs in facing the challenges and opportunities of the digital economy. These findings reinforce previous research emphasizing the vital role of leadership in the sustainability and competitiveness of small businesses in the digital transformation era.